Streptococcus lutetiensis inhibits CD8+ IL17A+ TRM cells and leads to gastric cancer progression and poor prognosis - Huiyu Wang; Wenhua You; Zining Zhu; Yuhan Zhang; Chupeng Hu; Jinying Lu; Yeding Huang; Rui Peng; Ruimin Shan; Ran Li; Yun Chen; Fuzhen Qi; et al. (npj Precision Oncology)
Abstract In many solid tumours, including gastric cancer (GC), the beginning and progression of the tumour are closely correlated with the tumour microbiome. Here, we show the changes in the gastric microbiota and their influence on immune regulation and the promotion of GC progression through 16s rRNA sequencing and single cell RNA sequencing. Streptococcus lutetiensis (S. lutetiensis) was found to be enriched in the tumour tissues of GC patients. Further analysis using single-cell sequencing and flow cytometry showed that S. lutetiensis notably affects the antitumour immunity by suppressing IL17 signalling and reducing the population of CD8+IL17A+ tissue-resident memory T (TRM) cells by activating Nrf2-mediated oxidative stress response. Mouse models confirm S. lutetiensis promotes GC progression by impairing immune responses in CD8+IL17A+TRM cells, suggesting it as a potential GC prognosis indicator and immunotherapy target, highlighting the microbiome's role in cancer progression.